Five-year outcome and safety in patients treated with immune checkpoint blockade therapies for urothelial carcinoma: Experience from real-world clinical practice - Tural, Deniz; Arslan, Çağatay; Selçukbiricik, Fatih; Ölmez, Ömer Fatih; Akar, Emre; Erman, Mustafa; Ürün, Yüksel; Erdem, Dilek; Karadurmuş, Nuri; Kılıçkap, Saadettin (CIG Media Group, 2023)
This 5-year analysis of real-world data confirms the durable response and long-term survival with ICTs in a broader range of patients with metastatic urothelial carcinoma. After 24 months, PFS and OS curves remained nearly flat. The safety profile was consistent with previous reports, and no new safety signals were observed. Background: In this study, we report real-world results from the 5-year follow-up data of urothelial carcinoma patients treated with immune checkpoint blockade therapies (ICTs). Patients and Methods: Metastatic urothelial carcinoma patients treated with at least one course of ICT were included in the study. The primary endpoint was overall response rate (ORR), and secondary endpoints were overall survival (OS), progression-free survival (PFS), duration of treatment with ICT, and safety. Median follow-up, PFS, and OS were estimated by using the Kaplan-Meier method. Results: Data of 201 eligible patients were analyzed. The median age of the patients was 66 (37-86) years, and 156 (84.3%) were male. The majority of patients (94.6%) had Eastern Cooperative Oncology Group (ECOG) PS scores of 0 to 1 and primary tumor in the bladder was predominant (87.5%). The median follow-up time was 54 (1.15-65) months. The rate of complete response (CR) to ICT, partial response (PR) rate, and ORR were 10.4% (n = 21), 22.4% (n = 45), and 32.4% (n = 66), respectively. The median duration of response (DOR) was 34.8 months (95% confidence interval [CI], 29.2-42.1). Of the 66 patients who responded to treatment, 28 (42%) had an ongoing response at the time of the analysis. Median PFS and OS were 3.8 (2.6-5.8) months and 9.4 (7.4-11.4) months, respectively. The 5-year PFS and OS rates were 9.8% and 12.8%, respectively. Fifty-eight percent of patients experienced a treatment-related adverse event of any grade, and 33 (16.4%) patients had a grade 3 to 4 adverse event. Conclusion: This 5-year analysis of real-world data confirms the durable response and long-term survival with ICT in metastatic urothelial carcinoma patients.
Keywords: Durability of Antitumor Activity and Safety; Immune Checkpoint Blockade Therapies; Long-Term Survival; Metastatic Urothelial Carcinoma; Outcomes